Two Gamispatulus Thatcher & Boger, 1984 (Cyclopoida: Ergasilidae) from Schizodon intermedius Garavello & Britski (Actinopterygii: Anostomidae), with description of a new species - Narciso, Rodrigo B. [UNESP]; Da Silva, Reinaldo José [UNESP] (Magnolia Press, 2020)
A parasitological survey of fishes from two tributaries (Veados and Paranapananema Rivers) of the Jurumirim Reservoir, Upper Paranapanema River, São Paulo State, Brazil, was carried out a during a sampling survey in 2011 and 2012. Several ectoparasitic copepods were found inside the nostrils of the freshwater anostomid fish, Schizodon intermedius Garavello & Britski, 1990. The morphological analysis of the copepod specimens indicated that they represent two species of the ergasilid genus Gamispatulus Thatcher & Boeger, 1984: Gamispatulus schizodontis Thatcher & Boeger, 1984 (type species) and an undescribed species, Gamispatulus ferrilongus n. sp., which are described herein. The present specimens of G. schizodontis agree in several respects with its original description; however, some differences were found regarding the morphology of mouthparts and the ornamentation of legs and antennules. These differences were not sufficient to propose a new species for this genus. However, it could indicate the need for reassessment of the type material to have a more complete representation of this species. Gamispatulus ferrilongus n. sp. shares several similarities with its congener G. schizodontis but the new species can be readily distinguished from its congener in having a unique combination of diagnostic features including: a long rostral spine with tip extending up to half of cephalothorax, simple retrostylets (lacking adjacent spatulate processes), and dorsal surface of genital double-somite with 2 rounded processes (anterior and posterior) on both lateral margins. A host-parasite list for all vaigamid genera and species is included.
Keywords: Copepoda; Crustacea; Freshwater; Jurumirim reservoir; Neotropical region; Paranapanema river; Taxonomy